Shelter Color Selection of Juvenile Swimming Crabs (Portunus trituberculatus) - Hanzun Zhang; Boshan Zhu; Liye Yu; Fang Wang (Fishes, 2022)
Color preference testing for animals is a prerequisite for optimizing facilities and ensuring animal welfare in aquaculture. Swimming crabs (Portunus trituberculatus) are aggressive, and shelters are often installed in ponds to reduce the high mortality rate caused by their agonistic behavior. To test the preference of juvenile crabs for the color of shelters, this study observes the preferences of crabs for shelters of different colors (white, yellow, blue, and black). The counts and duration of crabs occupying different colored shelters were quantified. The probability of fighting and the probability of abandoning the shelter were also calculated. The results revealed that: (i) when all colors were presented simultaneously, the z-scores of the blue shelters were far higher than others during the day; (ii) when only one color was present, crabs occupied the blue shelter significantly more often and for longer periods of time than others during the day, with invasive crabs exacerbating this preference; and (iii) the probability of fighting between crabs was relatively low in the presence of the blue shelter, and the probability of abandoning the shelter was significantly lower than that of others. Based on these results, blue shelters are recommended for use in swimming crab ponds.